The “white globe appearance” (WGA): a novel marker for a correct diagnosis of early gastric cancer by magnifying endoscopy with narrow-band imaging (M-NBI) - Doyama, Hisashi; Yoshida, Naohiro; Tsuyama, Sho; Ota, Ryosuke; Takeda, Yasuhito; Nakanishi, Hiroyoshi; Tsuji, Kunihiro; Tominaga, Kei; Tsuji, Shigetsugu; Takemura, Kenichi; Yamada, Shinya; Katayanagi, Kazuyoshi; Kurumaya, Hiroshi; Iwashita, Akinori; Yao, Kenshi (Endoscopy International Open, 2015)
Background and study aims: Although magnifying endoscopy with narrow-band imaging (M-NBI) is useful for the diagnosis of gastric mucosal lesions, differentiating between early cancer (EC) and low grade adenoma (LGA) remains a challenge. During M-NBI examination, we have noted the presence of a small, white lesion with a globular shape underneath cancerous gastric epithelium, and have termed this endoscopic finding the “white globe appearance” (WGA). The aim of this study was to determine whether or not the WGA could be an endoscopic marker for distinguishing EC from LGA.Methods: We retrospectively analyzed both the M-NBI scans and resected specimens of a total of 111 gastric lesions from 95 consecutive patients. Our main outcome was a difference in the prevalence of the WGA in EC and LGA.Results: The prevalence of the WGA in EC and LGA was 21.5 % (20 /93) and 0 % (0 /18), respectively (P = 0.039). The sensitivity, specificity, positive predictive value, and negative predictive value for differentiating between EC and LGA, according to the presence of the WGA, were 21.5, 100, 100, and 19.8 %, respectively.Conclusion: A positive WGA in a suspicious lesion on M-NBI would be an adjunct to the M-NBI diagnosis of possible EC because the specificity and positive predictive value of the WGA for differentiating between EC and LGA were extremely high. The WGA could be a novel endoscopic marker for differentiating between EC and LGA.